Діагностична модель “ОСОБИСТІСТЬ – ПОТЕНЦІАЛ – РОЗВИТОК” – основа формування стратегії розвитку кадрового потенціалу вищого навчального закладу - Тугай, А. М.; Гойко, А. Ф.; Єлішевич, М. А.; Криштоф, С. Д.; Воронюк, О. І. (Ways to Improve Construction Efficiency, 2014)
A theoretical and methodological approach to strategy development of human resources of higher education institutions (HEIs), as a key component of the overall strategy of any educational institution based diagnostic model "Personality - Capacity - Development".